PERILAKU KEUANGAN GENERASI MILENIAL DI KOTA DENPASAR : PENGARUH LITERASI KEUANGAN, ADOPSI FINTECH PAYMENT, IMPULSIVE BUYING DAN FINANCIAL SELF EFFICACY - Ketut Tanti Kustina; Ni Putu Ayu Sulasmi; Putu Pande R. Aprilyani Dewi; Gine Das Prena (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to analyze the influence of several factors on the financial behavior of the millennial generation in Denpasar City. The variables focused on include financial literacy, fintech payment adoption, impulsive buying, and financial self-efficacy. The goal is to evaluate the impact of these variables on the financial behavior of the millennial generation in the city of Denpasar. With an emphasis on these factors, this study is expected to provide a deeper understanding of the contribution to the financial behavior patterns of the millennial generation, especially in the